2020
DOI: 10.1590/0100-29452020008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mandarin hybrids grafted on 'Rangpur' lime in the Coastal Tablelands, Brazil

Abstract: The production of mandarins is incipient in Northeastern Brazil in spite of the large regional market. Few studies have reported the performance of mandarins under the tropical conditions in Brazil, considering that, in general, the quality and yield of these fruits are more expressive in regions of subtropical and Mediterranean climates. In this work, tree size, fruit production and quality of four mandarin hybrids (‘Piemonte’ mandarin-tangor, ‘Murcott’ tangor and ‘Page’ and ‘Nova’ tangelo-mandarin) grafted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The ratio, or maturi ty index, expresses fruit ripeness and is also an indi cator of flavor (Lado et al, 2018;Ribeiro et al, 2020). These fruit quality traits may be influenced by the scion variety, management practices, maturity level, climate, and rootstocks (AlMohuei and Choumane, 2014;Carvalho et al, 2020;Ribeiro et al, 2020;TiradoCorbalá et al, 2020). Here, we showed that FW, FD, and juice yield did not differ among the sweet orange varieties.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The ratio, or maturi ty index, expresses fruit ripeness and is also an indi cator of flavor (Lado et al, 2018;Ribeiro et al, 2020). These fruit quality traits may be influenced by the scion variety, management practices, maturity level, climate, and rootstocks (AlMohuei and Choumane, 2014;Carvalho et al, 2020;Ribeiro et al, 2020;TiradoCorbalá et al, 2020). Here, we showed that FW, FD, and juice yield did not differ among the sweet orange varieties.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the TSS content is the basis for the pay ment of a premium price differential for highquality fruit (Zhang and Ritenour, 2016). The ratio, or maturi ty index, expresses fruit ripeness and is also an indi cator of flavor (Lado et al, 2018;Ribeiro et al, 2020). These fruit quality traits may be influenced by the scion variety, management practices, maturity level, climate, and rootstocks (AlMohuei and Choumane, 2014;Carvalho et al, 2020;Ribeiro et al, 2020;TiradoCorbalá et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…18,20,41 However, similar to the North states, the narrow temperature range in the Northeast region does not favor fruit skin pigmentation. 53 The states of Goiás, Mato Grosso do Sul, Mato Grosso and Distrito Federal, which constitute the Central-West region, exhibited relatively cooler temperatures, with averages below 25 °C, during…”
Section: Resultsmentioning
confidence: 99%
“…When the air temperature exceeds 33 °C, which is outside the optimal range for spore germination, the conditions become unfavorable for disease spread 18,20,41 . However, similar to the North states, the narrow temperature range in the Northeast region does not favor fruit skin pigmentation 53 …”
Section: Resultsmentioning
confidence: 99%